Improved Clay, and its use in the Development of Local Architecture - د. مجدي محجوب سعد (White Nile Journal for Studies and Research, 2017)
This research is one of the eminent studies that aims to develop the construction with mud technology to solve economic, social and environmental problems of local architecture. Local architecture characterized by a unique architectural style, taken from the Western and the Eastern civilizations. Introducing mud architecture effectively, as one of the most important solutions to the problem of housing and sustainable development in the contemporary world. There is possibility of building towers using mud, counting to eight floors.